Development of a novel histone deacetylase inhibitor unveils the role of HDAC11 in alleviating depression by inhibition of microglial activation - Baek, Soo Yeon; Lee, Jeehee; Kim, Taegwan; Lee, Hyelim; Choi, Hoon Seong; Park, Hahnbeom; Koh, Minseob; Kim, Eunha; Jung, Michael E.; Iliopoulos, Dimitrios; Lee, Jeong Yeon; Kim, Jonghoon; et al. (Biomedicine and Pharmacotherapy, 2023)
Histone deacetylases (HDACs) are key epigenetic regulators and classified into four subtypes. Despite the various roles of each HDAC isoform, the lack of selective HDAC inhibitors has limited the elucidation of their roles in biological systems. HDAC11, the sole class-IV HDAC, is highly expressed in the brain, however, the role of HDAC11 in microglia is not fully understood. Based on the modification of MC1568, we developed a novel HDAC inhibitor, 5. Interestingly, 5 suppresses lipopolysaccharide-induced microglial activation by the initiation of autophagy and subsequent inhibition of nitric oxide production. Furthermore, we demonstrated that 5 significantly alleviates depression-like behavior by inhibiting microglial activation in mouse brain. Our discovery reveals that specific pharmacological regulation of HDAC11 induces autophagy and reactive nitrogen species balance in microglia for the first time, which makes HDAC11 a new therapeutic target for depressive disorder.
Keywords: Animals; Brain; Depression; Histone Deacetylase 2; Histone Deacetylase Inhibitors; Histone Deacetylases; Mice; Microglia; Depressive disorder; HDAC inhibitor; Microglial activation; Neuroinflammation